2021
DOI: 10.31557/apjcp.2021.22.12.3763
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Long Non Coding RNA ANRIL and SNHG14 in Acute Myeloid Leukemia

Abstract: Background: Long non-coding RNAs (lnRNAs) play a pivotal role in various malignancies including AML. Therefore, we decided to study both lnRNA ANRIL and lnRNA SNHG14 gene expressions in patients with AML to better understand their role in AML risk development, clinical presentation, and prognosis. Methods: The current prospective study included two hundred participants, 100 AML patients and 100 control subjects. Bone marrow analysis was made to all patients, in addition to gene expression molecular testing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The prognostic value of SNHG14 was also confirmed in acute myeloid leukemia which was associated with adverse overall survival (Gamaleldin et al 2021). More importantly, SNHG14 has also been identified as a neuro-related lncRNA that has been reported to regulate nerve cell apoptosis, protect cerebral injury, and regulate nervous system diseases, such as Parkinson's disease and neuroinflammation (Jiang et al 2021;Tan et al 2023;Zhang et al 2019a).…”
Section: Discussionmentioning
confidence: 93%
“…The prognostic value of SNHG14 was also confirmed in acute myeloid leukemia which was associated with adverse overall survival (Gamaleldin et al 2021). More importantly, SNHG14 has also been identified as a neuro-related lncRNA that has been reported to regulate nerve cell apoptosis, protect cerebral injury, and regulate nervous system diseases, such as Parkinson's disease and neuroinflammation (Jiang et al 2021;Tan et al 2023;Zhang et al 2019a).…”
Section: Discussionmentioning
confidence: 93%
“…For example, an expression study of HOTAIRM1 in 241 AML patients revealed its association with shorter overall survival, shorter leukemia-free survival, and higher cumulative incidence of relapse (Díaz-Beyá et al, 2015); its expression was also correlated with 33 microRNA signatures, which can be combined and used as a diagnostic marker for stratifying patients into high, intermediate, and low risk groups (Díaz-Beyá et al, 2015). Two separate studies analyzing bone-marrow samples from 178 and 100 AML patients found ANRIL overexpression compared to healthy donors (Tan et al, 2020;Gamaleldin et al, 2021). ANRIL is also associated with low rates of complete remission (CR) and overall survival (OS) along with FLT3 mutation, implying that it could be a valuable prognostic marker for AML (Tan et al, 2020;Gamaleldin et al, 2021).…”
Section: Lncrnas As Biomarkers In Myeloid Leukemiamentioning
confidence: 99%
“…Frontiers in RNA Research frontiersin.org and CML patients have been suggested as prognostic markers for early diagnosis (Table 3) (Wang et al, 2014;Wang X. et al, 2018;Díaz-Beyá et al, 2015;Hao and Shao, 2015;Wu et al, 2015;Fernando et al, 2017;Yao et al, 2017;Ma et al, 2020Ma et al, , 2018Zhang T. et al, 2018;Zhang W. et al, 2020;Zhang X. et al, 2020;Zhang F. et al, 2020;Izadifard et al, 2018;Jia et al, 2018;Pashaiefar et al, 2018;Qin et al, 2018Qin et al, , 2022Yang et al, 2018;Papaioannou et al, 2019b;Cai et al, 2019;Chen et al, 2019;El-Khazragy et al, 2019;Huang et al, 2019;Lei et al, 2019;Li et al, 2019;Sellers et al, 2019;Zhang and Tao, 2019;Feng et al, 2020b;Chen et al, 2020;Ketab et al, 2020;Peng et al, 2020;Qu et al, 2020;Tan et al, 2020;Xu et al, 2020;Gao, 2021a;Saad et al, 2021;Gamaleldin et al, 2021;Masoud Eslami et al, 2021;Pavlovic et al, 2021;…”
Section: Lncrnas As Biomarkers In Myeloid Leukemiamentioning
confidence: 99%
See 1 more Smart Citation